2020
DOI: 10.21037/atm-20-4055
|View full text |Cite
|
Sign up to set email alerts
|

Combination of mini locking plate and nitinol arched shape-memory connector for purely lateral malleolus fractures: technique and clinical results

Abstract: Background: Lateral malleolus fractures occur frequently. The common techniques for fixing purely lateral malleolus fractures are often challenging, owing to the extent of soft tissue damage and fracture non-union. Herein, we report a new treatment that entails minimally invasive insertion and continuous compression of the broken ends as a novel technique, and evaluate its clinical results. Methods: This study enrolled 21 patients (13 males and 8 females; mean age 32.06±3.45 years, range 23-69 years) with pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Xia et al [ 15 ] found an AOFAS score of 88 in 21 patients with ages ranging from 23 to 69 years, with purely lateral malleolus fractures. Each patient underwent ORIF with a mini-locking plate for internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al [ 15 ] found an AOFAS score of 88 in 21 patients with ages ranging from 23 to 69 years, with purely lateral malleolus fractures. Each patient underwent ORIF with a mini-locking plate for internal fixation.…”
Section: Discussionmentioning
confidence: 99%